New forms of political culture: an anomalous turnaround of social networks - Fernández Rubiño, Eduardo (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
In this interview with Eduardo Fernández we analyze the progressive use of social networks in Madrid, which became a mass phenomenon with the 15M Movement and has turned out to be a constituent part of Podemos’ media success. A sharp increase in numbers of followers and activity can be observed, along with the importance of social networks in both the creation of an organizational structure and the coordination with territorial Circles. Eduardo Fernández shows a high level of creativity in his management of social media, going beyond the usual corporate-stylecommunity management.